Evaluation of Association between Maxillary Posterior Teeth Periapical Pathologies and Maxillary Sinus Mucosal Changes—A Cone-Beam Computed Tomography (CBCT) Study - Kaimal, Vinitha G.; Patil, Bharati (Indian Journal of Radiology and Imaging, 2023)
Introduction Odontogenic infections are one of the common causes of maxillary sinusitis. With the close proximity of the roots of maxillary posterior teeth to the sinus floor, the infection may spread into the sinus causing sinus mucosal thickening. This study aims to evaluate the association between maxillary posterior teeth periapical pathologies and maxillary sinus mucosal changes using cone-beam computed tomography (CBCT) images.Methods One-hundred six maxillary posterior teeth with periapical lesions were included in this study and were assessed using CBCT images by two maxillofacial radiologists. The proximity of the roots to the sinus floor, the proximity of the top edge of the periapical lesion to the sinus floor, and the sinus mucosal changes associated with the periapical lesions were studied. The size of the periapical lesion was measured and scored using CBCT periapical index. Mucosal thickening more than 2 mm was considered pathological and the type, pattern, and severity of mucosal thickening were assessed. Data were analyzed using chi-squared tests at a level of significance set at p-value less than 0.05.Results Among the 106 teeth with periapical lesions, 99 teeth (93.4%) revealed the presence of maxillary sinus mucosal thickening. The prevalence of mucosal thickening increased significantly with the presence of cortical bone destruction, the close proximity of the root, and the periapical lesion to the sinus floor. The generalized type of mucosal thickening was more prevalent with larger periapical lesions and a significant increase in the severity of the thickening was observed closer spatial relationship of the root to the sinus floor.Conclusion Periapical pathologies of maxillary posterior teeth often cause sinus mucosal thickening. The early diagnosis and management of these pathologies will be helpful in preventing the spread of infection into the maxillary sinus.
Keywords: cone-beam computed tomography; maxillary sinus; mucosal thickening; periapical pathologies